Peritoneal Dialysis is Limited by Kidney and Liver Volume in Autosomal Dominant Polycystic Kidney Disease. Issue 3 (22nd January 2015) - Hamanoue, Satoshi; Hoshino, Junichi; Suwabe, Tatsuya; Marui, Yuji; Ueno, Toshiharu; Kikuchi, Koichi; Hazue, Ryo; Mise, Koki; Kawada, Masahiro; Imafuku, Aya; Hayami, Noriko; Sumida, Keiichi; et al.
Abstract We evaluated the influence of kidney volume (KV) and liver volume (LV) on continuation of peritoneal dialysis (PD) in patients with autosomal dominant polycystic kidney disease (PKD). Twenty‐two PKD patients on PD were retrospectively investigated after being divided into two groups. Group 1 comprised 15 patients who started PD at our hospital and group 2 was composed of seven patients referred from other hospitals for treatment of renomegaly by transcatheter arterial embolization (TAE) at 47.1 ± 21.8 months after commencing PD. In group 1, KV for both kidneys (mean ± SD) was 2787 ± 1945 mL (range: 1043 to 6816 mL), LV was 2198 ± 1139 mL (1005 to 4116 mL), and the total organ volume (TV = KV + LV) was 4985 ± 1815 mL (2320 to 8912 mL). In the patient with the largest TV from group 1 (KV of 6816 mL, TV of 8912 mL, and TV/BMI ratio of 426, PD was stopped due to dialysate leakage. However, dialysate leakage did not occur in the other 14 patients (TV ≦ 7963 mL and TV/BMI ratio of 353 at the start of PD). In group 2, KV was 5822 ± 1597 mL (3832 to 8862 mL), LV was 1776 ± 519 mL (1271 to 2671 mL), and TV was 7597 ± 1431 mL (5505 to 10358) before TAE. Leakage of dialysate did not occur with a mean infusion volume of 1530 ± 370 mL (1000 mL to 2000 mL), even after renomegaly and hepatomegaly progressed to the maximum TV/BMI ratio of 359. Six patients from the two groups developed new abdominal hernias at 36 ± 5 months (6–55 months) after starting PD. These findings suggest that performance of PD may be limited by renomegaly and hepatomegaly in patients with PKD.